A multicenter randomized phase 4 trial comparing sodium picosulphate plus magnesium citrate vs. polyethylene glycol plus ascorbic acid for bowel preparation before colonoscopy. The PRECOL trial - D’Angelo, Valentina; Piccirillo, Maria Carmela; Di Maio, Massimo; Gallo, Ciro; Bucci, Cristina; Civiletti, Corrado; Di Girolamo, Elena; Marone, Pietro; Rossi, Giovanni Battista; Tempesta, Alfonso Mario; Tracey, Maura C.; Romano, Marco; et al. (Frontiers in Medicine, 2022)
Background: Adequate bowel preparation before colonoscopy is crucial. Unfortunately, 25% of colonoscopies have inadequate bowel cleansing. From a patient perspective, bowel preparation is the main obstacle to colonoscopy. Several low-volume bowel preparations have been formulated to provide more tolerable purgative solutions without loss of efficacy. Objectives: Investigate efficacy, safety, and tolerability of Sodium Picosulphate plus Magnesium Citrate (SPMC) vs Polyethylene Glycol plus Ascorbic Acid (PEG-ASC) solutions in patients undergoing diagnostic colonoscopy. Methods: In this phase 4, randomized, multicenter, two-arm trial, adult outpatients received either SPMC or PEG-ASC for bowel preparation before colonoscopy. The primary aims were quality of bowel cleansing (primary endpoint scored according to Boston Bowel Preparation Scale) and patient acceptance (measured with 6 visual analogue scales). The study was open for treatment assignment and blinded for primary endpoint assessment. This was done independently with videotaped colonoscopies reviewed by 2 endoscopists unaware of study arms. A sample size of 525 patients was calculated to recognize a difference of 10% in the proportion of successes between the arms with a two-sided alpha error of 0.05 and 90% statistical power. Results: Overall 550 subjects (279 assigned to PEG-ASC and 271 assigned to SPMC) represented the analysis population. There was no statistically significant difference in success rate according to BBPS: 94.4% with PEG-ASC and 95.7% with SPMC (P=0.49). Acceptance and willing to repeat colonoscopy were significantly better for SPMC with all the scales. Compliance was less than full in 6.6% and 9.9% of cases with PEG-ASC and SPMC, respectively (P=0.17). Nausea and meteorism were significantly more bothersome with PEG-ASC than SPMC. There were no serious adverse events in either group. Conclusions: SPMC and PEG-ASC are not different in terms of efficacy, but SPMC is better tolerated than PEG-ASC. SPMC could be an alternative to low-volume PEG based purgative solutions for bowel preparation. This work was supported by the Italian Ministry of Health, Ricerca Corrente Funds, Linea 4/10 ClinicalTrials.gov NCT01649674; EudraCT 2011—000587—10.